2022
DOI: 10.1136/bmjqs-2021-014472
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of a multifaceted quality improvement intervention to improve patient outcomes after total hip and knee arthroplasty: a registry nested cluster randomised controlled trial

Abstract: ObjectiveTo assess the effectiveness of a prospective multifaceted quality improvement intervention on patient outcomes after total hip and knee arthroplasty (THA and TKA).DesignCluster randomised controlled trial nested in a national registry. From 1 January 2018 to 31 May 2020 routinely submitted registry data on revision and patient characteristics were used, supplemented with hospital data on readmission, complications and length of stay (LOS) for all patients.Setting20 orthopaedic departments across hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…SPC charts are then often used as an approach to measurement, where data will give feedback and inform further development of the intervention. Previous studies have shown that using SPC charts as part of the intervention (formative evaluation) can be effective to improve patient outcomes 28 29. Even though then primarily a tool for monitoring rather than to draw inferences about the effect of each implemented improvement initiative, this also requires planning the feedback, defining what constitutes special cause variation and so on.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…SPC charts are then often used as an approach to measurement, where data will give feedback and inform further development of the intervention. Previous studies have shown that using SPC charts as part of the intervention (formative evaluation) can be effective to improve patient outcomes 28 29. Even though then primarily a tool for monitoring rather than to draw inferences about the effect of each implemented improvement initiative, this also requires planning the feedback, defining what constitutes special cause variation and so on.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Methods have included: participant and provider self-report, reviewing attendance and other intervention records, direct observation and reviewing how many of the intervention components were used by participants. 3 8-10 Within healthcare service research, registry data (eg, Stephens et al 11 ) and selfreport methods (eg, van Schie et al 12 ) have been used to explore the use of implementation strategies within hospitals following quality improvement interventions. Self-report methods have also been used to determine whether patients enacted COVID-19 remote home monitoring activities (eg, Walton et al 13 ).…”
Section: Editorialmentioning
confidence: 99%
“…Once values align and clinicians are engaged, supports are needed to help close the intention-to-action gap. Action planning can be facilitated by identifying common barriers and proactively providing goal-oriented actions to overcome them—a strategy that has proven to significantly enhance the impact of CPF on clinical behaviour and patient outcomes 8 9. Leaders and those implementing CPF purposefully design and facilitate opportunities for clinicians to engage with their colleagues to share practices and identify those who may have discovered more effective strategies or approaches to care 10…”
Section: Introductionmentioning
confidence: 99%
“…It is important that this be designed for and embedded within existing workflows and care pathways35—guidance that is rarely put into practice. Additionally, design should account for clinician preferences which can be achieved using a participatory design approach to help illuminate values and beliefs and inform cointerventions 8 9 36. For example, understanding that the initial reaction to poor performance is shame can inform how feedback is framed and communicated to clinicians 36.…”
Section: Introductionmentioning
confidence: 99%